(untitled) (Latin American Journal of Sedimentology and Basin Analysis, 2022)
This work provides new U-Pb detrital zircon ages of the eastern synorogenic Upper Cretaceous deposits of the Neuquén Basin at Paso Córdoba, Río Negro, Argentina (Fig. 1). The Neuquén Basin is a large depocenter developed during the Late Triassic to Paleogene along the southwestern margin of Gondwana (30-40°S). It originated by continental-scale rifting processes resulting in the break-up of the Pangea supercontinent. It records a thick Mesozoic sedimentary succession more than 7,000 m thick including marine and non-marine sedimentary rocks. Important geodynamic changes occurred during the latest Mesozoic with the accelerated westward movement of the South American plate following its separation from the African plate, and the continuation of subduction processes along its western margin, most notably the convergence between the Nazca-Farallón and the South American plates. This new compressive tectonic setting triggered the foreland basin deposition of the Neuquén Group. The non-marine Neuquén Group shows an important regional distribution and is characterized as the first foreland basin deposits linked with the early uplift of the Andean orogen at ca. 100 Ma. The Neuquén Group contains an important fossil record and is a reservoir rock in some depocenters of the basin. For this reason, it has been a well-studied unit in both the southern and central parts of the basin. Regionally, this stratigraphic unit is covered by Maastrichtian to Paleocene marine facies of the Malargüe Group. The Upper Cretaceous non-marine deposits of the Neuquén Basin have an important exposure in Paso Córdoba area (General Roca, Río Negro). According to Hugo and Leanza (2001), these deposits are included in the Bajo de la Carpa and Anacleto formations (Neuquén Group) and the overlying Allen Formation (Malargüe Group). These authors interpreted the contact between both groups as an erosional unconformity. Afterwards, Paz et al. (2014) and Díaz-Martínez et al. (2018) carried out detailed sedimentological and ichnological studies in the area, discussed the contact between both units and proposed a transitional passage between the Anacleto (lacustrine/fluvial facies) and Allen (aeolian facies) formations. The ages of the Anacleto and Allen formations are based on magnetostratigraphic and biostratigraphic data obtained in other localities to the west and north of the study area. Dingus et al. (2000) proposed an early-middle Campanian maximum depositional age for the Anacleto Formation (78.3 Ma) based on paleomagnetic studies in the Auca Mahuevo area (Neuquén). Furthermore, levels assigned to the overlying Allen Formation in the Lago Pellegrini area (Río Negro), contain an ostracod fauna from the upper Campanian-lower Maastrichtian interval (Ballent, 1980). In this contribution, we use a sedimentological and geochronological approach to discuss the paleoenvironment, provenance and age of the Anacleto Formation in the Paso Córdoba area. The facies analysis carried out in this work corroborates the proposal made by Paz et al. (2014) and by Díaz-Martínez et al. (2018), allowing the recognition of three facies associations: (I) lacustrine, (II) wet interdunes and (III) dunes and dry interdunes (III), indicating an increase in the aridity of the depositional system towards the top of the studied succession. In particular, the sample APC01-20 dated by U-Pb in detrital zircons was collected from the bottom of wet interdunes facies association (II) given its textural features and its importance in terms of their stratigraphic position (Fig. 1D and 2D). According to the frequency histogram and relative probability plot of detrital zircon ages obtained from APC01-20 sample analysis, a multimodal pattern of ages can be distinguished. The sample is represented by five main populations; 75 – 126 Ma (Cretaceous, 32%), 150 – 200 Ma (Jurassic, 31%), 254 – 282 Ma (Permian, 10%), 300 – 349 Ma (Carboniferous, 14%) and 358 - 405 Ma (Devonian, 11%). The sample also contains two isolated ages that represent 2% of the total (478 Ma, Ordovician and 1,217 Ma, Mesoproterozoic). The main peak (32%) corresponds to latest Early-Late Cretaceous zircons with a youngest graphical peak (YPP) of 81.9 Ma (Campanian) (Fig 2A). For the calculation of the maximum depositional age, different ways of measurement were considered (Dickinson and Gehrels, 2009). As a result of data analysis, weighted mean average of the youngest cluster of two or more grain ages that overlap at 1? uncertainty, was the estimation that was better adjusted for the sample. The age calculation based on a sample of young Cretaceous zircons (n=11) pointed towards a maximum depositional age of 78.6 ± 1.7 Ma (middle Campanian) for the Anacleto Formation. The number of zircons used for the calculation of the maximum depositional age, together with the morphology of the measured crystals, suggest a coeval volcanic activity during the deposition of Anacleto Formation.